ANALYSIS OF ONLINE E-COMMERCE MARKETING AND DIGITAL MARKETING IN CONSUMER INTEREST TO BUY SHOES PRODUCTS IN THE KARAWANG REGION - Etty Zuliawati Zed; Zulfa Zakiatul Hidayah; Andrianto Prasetya Nugroho (Jurnal Ekonomi, 2023)
Running a business sometimes gets a big profit and sometimes gets a loss from a business. Technology and digital media that are increasingly developing have changed people's activities from offline shopping to online. The lack of marketing methods in a business and the company's lack of innovative strategies in product sales promotion result in high costs. This makes the company's cash depleted only for promotional activities. This study aims to determine the extent of the influence of online e-commerce marketing Tokopedia and digital marketing on the interest in buying Adidas shoes in Karawang. With the Equation Stuctural Equation Modeling (SEM) method, it can be used to estimate the direct, indirect and total effects. The study conducted by researchers is to measure the positive influence of several indicators on each variable in it by using a statistical test tool, namely Partial Least Square (PLS) using SmartPLS 3.0 software. The results of this study indicate that online marketing and digital marketing have a positive effect on buying interest.